Karyomapping: A single centre's experience from application of methodology to ongoing pregnancy and live-birth rates - Ben-Nagi, J; Wells, D; Doye, K; Loutradi, K; Exeter, H; Drew, E; Alfarawati, S; Naja, R; Serhal, P (Elsevier, 2017)
This study aimed to determine whether karyomapping can be applied to couples requiring preimplantation genetic diagnosis (PGD) for single gene disorder (SGD) and/or chromosomal rearrangement. 75/82 (91.5%) and 6/82 (7.3%) couples were referred for autosomal SGD and X-linked disease, respectively. One couple (1.2%) was referred for SGD and chromosomal rearrangement. Of 608 embryos, 146 (24%, 95% CI 21–28) day-3 and 462 (76%, 95% CI 72–79) blastocyst biopsies were performed. A total of 81 embryo transfers were performed; 16/81 (20%) were following day-3 embryo biopsy, 65/81 (80%) were following blastocyst biopsy and cryopreserved embryo transfer. Of 81 embryo transfers with known pregnancy outcome, 51 (63%, 95% CI 52–73) were on-going pregnancies, 6/81 (7%, 95% CI 3–15) resulted in first trimester miscarriages and 24/81 (30%, 95% CI 21–40) were failed implantations. Of the 51 on-going pregnancies, 15 (29%, 95% CI 19–43) couples had a singleton live birth at the time of write up. There have been no reports of abnormal prenatal, genetic testing or diagnosis of phenotype at birth. Karyomapping is reliable, efficient and accurate for couples requiring PGD for SGD and/or chromosomal rearrangement. Additionally, it provides aneuploidy screening, minimising risks of miscarriage and implantation failure.